Formulasi Pakan Lengkap (Complete Feed) Berbasis Limbah Pertanian Sebagai Pakan Ternak Kambing Di Kecamatan Kromengan Kabupaten Malang - Dyah Lestari Yulianti; Permata Ika Hidayati; Ahmad Shodiq (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
Farmers in Kromengan Village, Kromengan District, Malang Regency have problems providing forage feed for their goats. Appropriate technology offered on this community services program is the silage technology on agricultural by-product. A target of this community services programes is a group of goat farmers